2023
DOI: 10.3390/jof9020255
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Aspergillosis after Renal Transplantation

Abstract: Over 95,000 renal transplantation procedures were completed in 2021. Invasive aspergillosis (IA) affects about 1 in 250 to 1 in 43 renal transplant recipients. About 50% of cases occur in the first 6 months after transplantation; the median time of onset is nearly 3 years. Major risk factors for IA include old age, diabetes mellitus (especially if prior diabetic nephropathy), delayed graft function, acute graft rejection, chronic obstructive pulmonary disease, cytomegalovirus disease, and neutropenia. Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…We have not addressed the likely impact of azole/corticosteroid interactions, which may have acted to effectively boost corticosteroid exposure, in those taking prednisolone and voriconazole and methylprednisolone and itraconazole, as examples. Moreover, no study reported renal transplant loss related to withdrawal or not of corticosteroid therapy in the context of life-threatening fungal infection [112]. Future research could focus on the impact of corticosteroids on the outcome in renal transplant recipients and explore if reduction in steroid dose could have a positive impact on retaining renal allografts, without the patient dying.…”
Section: Discussionmentioning
confidence: 99%
“…We have not addressed the likely impact of azole/corticosteroid interactions, which may have acted to effectively boost corticosteroid exposure, in those taking prednisolone and voriconazole and methylprednisolone and itraconazole, as examples. Moreover, no study reported renal transplant loss related to withdrawal or not of corticosteroid therapy in the context of life-threatening fungal infection [112]. Future research could focus on the impact of corticosteroids on the outcome in renal transplant recipients and explore if reduction in steroid dose could have a positive impact on retaining renal allografts, without the patient dying.…”
Section: Discussionmentioning
confidence: 99%
“…9 Almost half of the cases (43%) occur in the first 6 months after transplantation, with a mortality of 40%-60%; 20%-25% of those who survive present graft loss. 8 HMPV in the SOT population causes 1.5-16.3 cases of respiratory infection per 1000 patients per year, representing 4.5% of all RVI. Cough and upper respiratory symptoms are common, and disease progression to pneumonia in a median of 7 days is common (49% of cases).…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillus infection has also been frequently described as associated with COVID‐19 15 . While a negative serum Aspergillus galactomannan can occur in the setting of a positive (1,3)‐β‐D‐glucan, the imaging is not typical in this case 17 . Yet, if this was a significant concern, a bronchoscopy with bronchoalveolar lavage (BAL) Aspergillus galactomannan could be helpful.…”
Section: Fungal Diagnostics: Nate Bahrmentioning
confidence: 94%